2013
DOI: 10.1136/bcr-2013-009018
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy after hydrosalpinx treatment with Essure

Abstract: We present a case of a 29-year-old woman, with a history of ectopic pregnancy, which required left salpingectomy, and with a tortuous and impermeable right fallopian tube, compatible with hydrosalpinx. As hydrosalpinx itself can compromise a future pregnancy, treatment with Essure was proposed before passing to medically assisted procreation techniques. Five months after placement of Essure in the right fallopian tube, an in vitro fertilisation cycle was successfully completed and the woman had a singleton pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…We further examined the remaining 64 records for eligibility. We excluded 29 studies (from 32 records) for the following reasons: one study (from one record) was still ongoing; six studies (from six records) were not written in a Western language; 14 studies (from 15 records) evaluated fewer than 10 women; six studies (from six records) had insufficient data to evaluate eligibility and the authors did not respond to our electronic attempt to contact them; and two studies (from four records) did not provide IVF results. Therefore, 26 studies (from 32 records) were considered eligible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We further examined the remaining 64 records for eligibility. We excluded 29 studies (from 32 records) for the following reasons: one study (from one record) was still ongoing; six studies (from six records) were not written in a Western language; 14 studies (from 15 records) evaluated fewer than 10 women; six studies (from six records) had insufficient data to evaluate eligibility and the authors did not respond to our electronic attempt to contact them; and two studies (from four records) did not provide IVF results. Therefore, 26 studies (from 32 records) were considered eligible.…”
Section: Resultsmentioning
confidence: 99%
“…A recently published review assessing the use of Essure for the management of hydrosalpinx prior to IVF included 11 studies. Six of them evaluated fewer than 10 patients, thus were not included in our review because of risk of publication bias. One further study was not included in our review because it reported insufficient data for the meta‐analysis, and the authors did not respond to our electronic attempts to contact them.…”
Section: Discussionmentioning
confidence: 99%
“…Use of Essure microinserts for therapeutic purposes (e.g., presence of hydrosalpinx or sactosalpinx) is largely supported by international literature and advocated by scientific societies as a safe, effective, and minimally invasive alternative to salpingectomy, whereas laparoscopic treatment is contraindicated [17][18][19][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Bien qu'en l'absence d'autorisation de mise sur le marché dans cette indication, l'efficacité et l'innocuité de l'occlusion tubaire proximale par micro-implants Essure 1 pour le traitement des hydrosalpinx ont dé jà é té dé montré es [6,10,11]. Tout en apportant les avantages de l'hysté roscopie par rapport à la coelioscopie, l'amé lioration des chances de grossesse et de naissances est comparable à la salpingectomie [4,6].…”
Section: Discussionunclassified